Parenting influences associated with BMI-for-age z-score of Malaysian children aged 6-36 months: a cross-sectional study based on an online survey - Wong, Hui Juan; Chin, Yit Siew; Lim, Poh Ying; Tan, Cin Cin (Nutrition Society of Malaysia, 2024)
Introduction: Malnutrition in early life can contribute to lifelong health consequences. Both fathers and mothers can influence children’s feeding, eating behaviours, and body weight status. This cross-sectional study aimed to determine the association between parental factors and body mass index-for-age z-score (BAZ) of Malaysian children aged 6-36 months. Methods: An online questionnaire using Google Form, which comprised of socio-demographic factors, parental lifestyle and feeding factors, children’s birth history and eating behaviours, was completed by 282 pairs of fathers and mothers of full-term children during the COVID-19 pandemic. Health records were accessed with parental consent to ensure accurate measurements of children’s weight and length, while both fathers and mothers self-reported their weight and height. Results: Prevalence of at-risk overweight, overweight, and obesity among children was 10.7%, 2.8%, and 1.1%, respectively, while wasting and severe wasting was 5.7% and 0.4%, respectively. Multiple linear regression analysis found that higher birth weight ( β=0.271, p<0.001), less frequent use of food to calm by fathers ( β=-0.127, p=0.035), and higher maternal BMI ( β=0.136, p=0.021) significantly contributed to higher BAZ among children. Conclusion: These findings suggest that interventions should involve both fathers and mothers with a focus on nutrition education in promoting responsive feeding, such as minimising use of food, to calm children. Additionally, efforts to ensure good nutrition before and during pregnancy to achieve ideal birth weight are equally important.